2013
DOI: 10.1093/cvr/cvt064
|View full text |Cite
|
Sign up to set email alerts
|

Dexfenfluramine and the oestrogen-metabolizing enzyme CYP1B1 in the development of pulmonary arterial hypertension

Abstract: AimsPulmonary arterial hypertension (PAH) occurs more frequently in women than men. Oestrogen and the oestrogen-metabolising enzyme cytochrome P450 1B1 (CYP1B1) play a role in the development of PAH. Anorectic drugs such as dexfenfluramine (Dfen) have been associated with the development of PAH. Dfen mediates PAH via a serotonergic mechanism and we have shown serotonin to up-regulate expression of CYP1B1 in human pulmonary artery smooth muscle cells (PASMCs). Thus here we assess the role of CYP1B1 in the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 43 publications
(67 reference statements)
3
73
0
1
Order By: Relevance
“…Increased synthesis of estrogen has been clinically associated with portopulmonary hypertension (15) and estrogen is causative in female susceptible models of PH (7)(8)(9). Studies into the role of estrogen in PAH have failed to reach a consensus, mainly because of the variety of experimental approaches adopted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased synthesis of estrogen has been clinically associated with portopulmonary hypertension (15) and estrogen is causative in female susceptible models of PH (7)(8)(9). Studies into the role of estrogen in PAH have failed to reach a consensus, mainly because of the variety of experimental approaches adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have described novel murine models where only female animals develop PH, such as mice overexpressing the serotonin transporter gene (SERT1 mouse) (7) and Mts1 (8). In these models the predominant circulating estrogen 17b-estradiol plays an essential role in the development of the PH phenotype (7)(8)(9). Estrogen can also induce proliferation of human pulmonary artery smooth muscle cell (hPASMCs) and may therefore contribute to the pulmonary artery remodeling observed in PAH (7,10).…”
Section: At a Glance Commentarymentioning
confidence: 99%
“…[5][6][7][8] There is an estrogen paradox however as while exogenous estrogen may be protective against experimental pulmonary hypertension (PH) and right ventricular (RV) hypertrophy in rodent models, [9][10][11][12] endogenous estrogen is causative in female animal models. [13][14][15][16][17] Estrogen is synthesized from testosterone through the enzyme aromatase and inhibition of aromatase attenuates experimental PH but only in females. 17 Estrogen can be metabolized through the cytochrome p450 1B1 (CYP1B1) enzyme to form the mitogenic 16α-hydroxyestrone, a metabolite established to be pathogenic in PH.…”
mentioning
confidence: 99%
“…In addition, TPH-1 knockout mice are protected from hypoxia-induced pulmonary hypertension (PH) (10,11). We have shown that only female mice develop PH via a serotonin-dependent mechanism-for example, mice overexpressing the serotonin transporter (SERT), calcium-binding protein S100A4/mts1-overexpressing mice, and mice dosed with dexfenfluramine (6,12,13). This PH phenotype is estrogen dependent, and suggests that female sex and estrogen influence the development of PH in these serotonin-dependent models.…”
mentioning
confidence: 99%